Feminists and queer theorists debate the future of critical management studies - Linstead, Alison, 1971-; Harding, Nancy, 1952-; Phillips, Mary, 1955- (Emerald Publishing Limited, 2017)
'What is CMS for and what might its future be- both inside the domain of academia and outside it? It's a question that has beguiled and frustrated academics within and outside its community. At the hear of CMS is an enduring skepticism concerning the social and ecological sustainability of prevailing ideas and forms of management and organization. Using ideas from feminist and queer theory, authors of this volume aim to generate some thinking and possibly a nascent agenda. It focuses on the future of CMS but also intertwines it with ideas as to how scholarly communities can engage in working lives differently.
Prelims -- Introduction: feminist and queer politics in critical management studies -- Manifesto for feminist critical race killjoys in CMS -- Redeeming difference in CMS through anti-racist feminisms -- Beyond subjectless abstractions: a feminist praxis contribution -- Feminist critical management studies in the lecture hall: a space for activism and hope? -- Feminism in the third space - Critical discourse analysis of Mipsterz women and grassroots activism -- The neoliberal crisis: alternative organizing and spaces of/for feminist solidarity -- Feminist CMS Writing as difficult joy: via bitches and birds -- Writing with eve: queering paper -- What's wrong with queer? between queer dialogue and separatist safe spaces -- Queer matters - reflections on the critical potential of affective organizing -- Critical management studies, queer theory and the prospect of a queer friendship -- Biographies -- Index.
Includes bibliographical references and index.
Print version record
Keywords: Business & Economics -- General; Business competition; Critical theory; Queer theory; Management